Lembaga Bantuan Hukum Bagi Hak Tersangka Dalam Pradilan Pidana di Indonesia - Yuneida, Setly Selva; Wardani, Retno Kusuma (Wajah Hukum, 2023)
Research aims to analyze the norms related to legal aid in legislation by providing legal protection for suspects and to analyze the role of legal assistance in legal protection of suspects in the criminal justice system in Indonesia. The problems to be examined are regarding the formulation of norms related to legal aid in legislation and the role of legal aid institutions in providing guarantee protection for suspects in the criminal justice system in Indonesia. Research uses a normative juridical approach by collecting primary, secondary and tertiary data. Research uses a conceptual approach and data analysis techniques by interpreting, assessing and evaluating. Based on this research, it was found that in the Criminal Procedure Code there are legal aid norms, in which there are still contradictions with one another (contradiction determinists), as well as provisions governing the role of legal aid, in this case, legal aid institutions have not played a good role, so many rights of suspects who are still neglected during the examination process.